2022
DOI: 10.3389/fsurg.2022.988331
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of pelvic sarcoma patients undergoing internal and external hemipelvectomy: A meta-analysis study

Abstract: IntroductionMalignant and giant pelvic tumors are complex and rare, and hemipelvectomies are complex procedures performed for this malignant lesion. Only a few studies had been conducted on the survival and recurrence of pelvic sarcomas patients undergoing internal or external hemipelvectomy. In the present study, we compared internal with external hemipelvectomy in pelvic sarcomas on clinical outcomes by a meta-analysis.MethodsThe survival and recurrence rates of pelvic sarcomas patients were collected from r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…It is quite difficult to standardize such a rare operation as the external hemipelvectomy. In a recent meta-analysis, only 5 studies of 183 patients were found to compare the results of internal and external hemipelvectomies over a span of 35 years [17]. The majority of even high volume cancer hospitals do not have significant numbers of these operations.…”
Section: Discussionmentioning
confidence: 99%
“…It is quite difficult to standardize such a rare operation as the external hemipelvectomy. In a recent meta-analysis, only 5 studies of 183 patients were found to compare the results of internal and external hemipelvectomies over a span of 35 years [17]. The majority of even high volume cancer hospitals do not have significant numbers of these operations.…”
Section: Discussionmentioning
confidence: 99%